Complications of classic double injection technique of peribulbar anaesthesia given in supine position before cataract surgery - Kapoor, Shilpi; Rather, Shagufta; Gupta, Dinesh (Asian Journal of Medical Sciences, 2021)
Background: Peribulbar anaesthesia has almost totally replaced general anaesthesia and retrobulbar block for ocular procedures especially in adults. Peribulbar block involves injections above and below the orbit, with local anesthetic deposited within the orbit but does not enter the muscle cone. Relatively safe but it is still associated with complications which are detailed in this study. Aims and Objective: To study the complications of classic double injection technique of peribulbar anaesthesia given in supine position before cataract surgery and to find the percentage of patients achieving complete block with 7ml of anaesthetic solution given by peribulbar route. Materials and Methods: This prospective observational study was conducted on 500 patients who were admitted for undergoing cataract extraction surgery in the Department of Ophthalmology in GMC Jammu for a period of 8 months from December 2018 to July 2019. Results: It was observed that 103 patients out of 500 (20.6%) developed one or more of complications. Chemosis was the most common complication which occurred in 87 (17.4%) patients followed by subcunjunctival haemorrhage observed in 19 (3.8%) patients. Lid ecchymosis occurred in 16 (2.4%) patients. Retrobulbar haemorrhage occurred in 11 (2.2%) patients. 2 (0.4%) patients developed severe lid edema. In 2 (0.4%) patients wrong eye was given block. 1 (0.2%) patient developed CRAO. Complete akinesia was obtained in 415 (83%) patients with 7ml of block. Rest required supplementary injections. 14 (2.8%) patients did not attain full akinesia after 12ml of block. Conclusion: Peribulbar block is a relatively safe procedure for obtaining ocular analgesia and akinesia, but is still associated with complications ranging from minor lid edema and chemosis to grave events like RBH to CRAO.